Review on Evolving Trends in Content Marketing - Pradhan, Bibhuti Bhusan (International Journal of Psychosocial Rehabilitation, 2019)
Content marketing is a kind of advertising that involves creating and transmitting online content (like images, forums, and news articles) which does not specifically support a product but is meant to create awareness in its goods or services. Nonetheless, there are still plenty of different points of view on what content marketing means and how it can be applied. Content marketing is commonly understood as exchanging product content through exclusive networks to obtain attention in an effort to persuade brand discussions to build more brand recognition, among others. Effective content marketing strategies is a systematic approach, but very few organizations adopt written instructions that hinder the progress. In the new, moving, knowledge powered world, content marketing develops to be a strong marketing technique. It’s not a new tactic and more and more companies are beginning to slowly participate throughout content marketing. Content marketing is becoming a pioneer in marketing scheme in digital advertising interaction, and uses customer’s perspective to form relationships by sharing content on social media that improves the everyday lives.